PERAN STANDAR AKUNTANSI PEMERINTAHAN DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KUALITAS INFORMASI LAPORAN KEUANGAN DAN AKUNTABILITAS KEUANGAN - Dewi, Nur Fitri (STIE Perbankan Indonesia, 2024)
This research aims to examine the influence of government accounting standards and internal control systems on the quality of local government financial report information and their impact on financial accountability. The data collection method used was a questionnaire distributed to 50 samples of the Depok City Regional Financial Agency. The collected data was processed using SPSS 27.00 with t test and Path Analysis. The research results show that government accounting standards and internal control systems have a positive effect on local government financial reports. Government accounting standards and internal control systems also have a positive effect on financial accountability, both directly and indirectly, mediated by the quality of local government financial report information. In addition, the quality of local government financial report information has a direct and positive effect on financial accountability. The results of this research can be useful for the government as input and consideration in determining policies, especially regarding improving the quality of information on government financial reports and financial accountability. Keywords: Government Accounting Standards, Internal Control Systems, Quality of Financial Report Information, Accountability